Long-Term Outcomes after Rotational Atherectomy for Calcified Chronic Total Occlusion versus Nonchronic Total Occlusion Coronary Lesions. (27th December 2022) - Elbasha, Karim; Mankerious, Nader; Alawady, Mohamed; Ibrahim, Ghada; Abdullah, Radwa; Abdel-Wahab, Mohamed; Hemetsberger, Rayyan; Toelg, Ralph; Richardt, Gert; Allali, Abdelhakim
Abstract : Background . The role of rotational atherectomy (RA) in contemporary percutaneous coronary intervention (PCI) is expanding to include certain chronic total occlusion (CTO) lesions. However, the long-term outcome of RA in CTOs is still unclear. Objective . To investigate in-hospital and long-term outcomes after RA for CTO compared to non-CTO calcified lesions. Moreover, this report evaluates the role of the elective RA approach in calcified CTOs. Methods and Results . This study enrolled 812 patients (869 lesions; CTO, n = 80 versus non-CTO, n = 789). The mean age of the study population was 73.1 ± 8.6 years, the baseline characteristics were comparable in both groups. Balloon-resistant CTO lesions represented the main indication for RA in CTO patients (61.2%). The mean J-CTO score was 2.42 ± 0.95. The angiographic success rate was lower in CTO patients (88.8% vs 94.9%; p = 0.022). In-hospital major adverse cardiac events (MACE) rate was comparable in both groups (CTO 8.8% vs 7.0% in non-CTO; p = 0.557). At two-year follow-up, a higher target lesion failure (TLF) was observed in CTO group (25.5% vs 15.1%, log rank p = 0.041), driven by higher cardiac mortality while the clinically driven target lesion revascularisation (TLR) was comparable between the study groups. Elective RA for CTO had a shorter procedural time and lower rate of dissection (7.5% vs 25%; p = 0.030) compared to bail-out RA with similar long-term outcomes. Conclusion . Compared to non-CTO, RA for CTO can be performed with a high procedural success rate and comparable in-hospital outcomes. Apart from higher cardiac mortality in the CTO group, the long-term outcomes are comparable in both groups. Elective RA is a feasible and beneficial approach to be used in CTO intervention.